THE INTERNET IS TRASH: MAKING SENSE OF TOXIC NETWORKS - Buck, Amber M.; Tekobbe, Cindy; Edwards, Dustin; Beck, Estee (AoIR Selected Papers of Internet Research, 2020)
This panel brings together scholars studying distinct aspects of internet culture in order to make sense of the negative byproducts of online spaces. Each presenter takes on a different topic: political internet memes, fan subcultures, conscious disconnection from internet platforms, and physical digital waste to consider the consequences of internet life. Using distinct methodologies: case study interviews, ethnography, textual studies and histories, and autoethnography, this panel considers what internet scholars can learn from the unsavory parts of the internet. Working with notions of internet waste, these presentations serve to build out a broad set of perspectives about the potential value in the trash internet, what we can learn from it, and how we can think more deeply about that which has little value or consideration in the internet life of clicks, posts, shares, likes, and follows. Through these presentations, the speakers ask the audience to consider their own views of internet garbage and to think about remedies to the toxic ecologies that impact life - both virtual and literal.